Cross-paradigms or word formation patterns in interface: evidence from Portuguese - Rodrigues, Alexandra Soares (2020)
Our aim is to demonstrate with Portuguese word-formation data collected from corpora that derivational paradigms are mental patterns dynamically organized around more than one axis in what we call cross-paradigms. Cross-paradigms are structured by affixes which may put different base-organized paradigms into interface. This hypothesis is supported by recent psycholinguistic approaches to the mental lexicon such as Libben (2014) (cf. Libben’s concepts on morphological transcendence and morphological superstates), according to whom the mental lexicon is not as an «inert knowledge store, [but] as a dynamic cognitive system that allows for lexical activity.» (Libben 2014: 209). Our hypothesis is also founded on linguistic works such as Corbin (1987), which, as demonstrated by Booij (2007), presents a paradigmatic perspective on word-formation, and on Blevins (2016). Following Štekauer (2014: 359), we consider derivational paradigms as «based on formal realization of a cognitive category by an affixation process.» According to Pounder (2000), different materials can organize each paradigm. It is not just a specific morpheme that functions as the axis of a certain paradigm. The axis may correspond also to the word-class, semantic rules, and other features labelled under ‘lexical paradigm’ by Pounder. Our work sticks to two main different paradigm relationships: the lexeme-base-class-organized paradigm and the affix-organized one. Giving examples from Portuguese, a lexeme-base-class organized paradigm is illustrated by deverbal nouns with different suffixes such as avaliação ‘evaluation’, matança ‘slaughter’, congelamento ‘freezing’, aterragem ‘landing’ and soldadura ‘soldering’. The axis of this paradigm corresponds to the base lexeme the nouns correlate with, which is a verb (avaliar ‘to evaluate’, matar ‘to kill’, congelar ‘to freeze’, aterrar ‘to land’, soldar ‘to solder’)